Polydimethylsiloxane-based wide-range mass calibration for direct analysis in real-time mass spectrometry - Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2013)
Direct analysis in real-time mass spectrometry (DART-MS) is normally applied for small-molecule analysis up to about m/z 1,000. Here, for the analysis of polydimethylsiloxanes, high-mass capabilities expanding beyond m/z 3,000 are demonstrated. In addition, polydimethylsiloxanes provide an ideal mass calibration standard for positive-ion DART-MS. A mass reference list has been compiled to cover ions from m/z 200 up to m/z 2,600. Species with more than 20 silicon atoms exhibit increasingly broader isotopic patterns with decreasing abundances of the monoisotopic ions. The use of the first isotopic peaks for analyte ions above m/z 2,000 serves as a work-around and ensures easy and reproducible recognition of the reference peaks by the instrument data system. Here, the positive-ion DART mass spectra of polydimethylsiloxanes and the corresponding experimental procedures are described, and the mass reference list is provided.